Pengaruh Lingkungan Kerja Fisik, Lingkungan Kerja Non-Fisik, dan Konflik Peran Terhadap Niatan Keluar (Studi Pada Karyawan PT X) - Pramesti, Fadiyah Indah; Yuniawan, Ahyar (Universitas Negeri Surabaya, 2025)
This study examines the impact of the work environment and role conflict on employees' intention to quit, employing a quantitative approach with data processed using the Smart PLS application. The research involved 100 respondents to explore how various aspects of the work environment, both physical and non-physical, along with role conflict, shape employees' decisions regarding whether to remain in or leave their organization. The findings indicate that the physical and non-physical work environments do not have a significant effect on employees' intention to quit, suggesting that environmental factors alone may not be the primary drivers of turnover decisions. However, role conflict was found to have a positive effect, highlighting the importance of clarity in job responsibilities and expectations. When employees face overlapping or unclear roles, dissatisfaction can increase, leading to a higher likelihood of departure. These results emphasize the need for organizations to address role ambiguity and implement clear job structures to enhance employee satisfaction, retention, and overall workplace stability.